2000
DOI: 10.1038/sj.bmt.1702527
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and behavioral adjustment after pediatric bone marrow transplantation

Abstract: Summary:The purpose of this study was two-fold: to describe the quality of life and behavioral adjustment of survivors of pediatric bone marrow transplantation (BMT) prior to and 6 months post-BMT; and, to identify correlates of survivors' quality of life and behavioral adjustment. Participants were 26 children and adolescents who underwent BMT, and their mothers. At pre-and 6 months post BMT, mothers completed standardized measures of their children's behavioral adjustment, quality of life, and adaptive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
113
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 16 publications
9
113
1
2
Order By: Relevance
“…An important predictor of proxy-rated HRQoL was found in the child's demandingness perceived by the parents, assessed before and after admittance for SCT. The low post-SCT HRQoL ratings we found are in contrast with results reported in several other studies [6,15,28] in which an improved HRQoL was found after 6 months or more. One explanation for this difference could be the number of assessments done in some of these studies [15,34].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…An important predictor of proxy-rated HRQoL was found in the child's demandingness perceived by the parents, assessed before and after admittance for SCT. The low post-SCT HRQoL ratings we found are in contrast with results reported in several other studies [6,15,28] in which an improved HRQoL was found after 6 months or more. One explanation for this difference could be the number of assessments done in some of these studies [15,34].…”
Section: Discussioncontrasting
confidence: 99%
“…Research has shown that parents of children undergoing SCT can suffer from posttraumatic stress symptoms [25,27], depression [6,26], distress [35,39], and anxiety [6,25]. Maternal post-SCT anxiety and depression scores have been found to correlate with their children's QoL ratings at 6 months post-SCT [6]. It has been suggested that maternal psychological problems could be a result of their children's ongoing medical problems and subsequent reduced QoL [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations